PENGARUH PROFITABILITAS DAN GOOD CORPORATE GOVERNANCE TERHADAP MANAJEMEN PAJAK - Helentina; Harman Malau (Jurnal Ekonomis, 2021)
This study aims to determine wheter there is an influence between Profitability and Good Corporate Governance on Tax Management. The research population is banking sector companies listed on the Indonesia Stock Exchange in 2017-2019, which where taken as many as 23 companies as samples. The data used by the researchers as the basis of analysis in this study is secondary data. The analysis technique used by the researchers is multiple linear regression analysis. The result of the study show that Profitability and Good Corporate Governance have no significant effect on tax management.